THE ETHICS OF BURDEN SHARING: WHEN CANADA TALKS ABOUT FAIRNESS, BUT ACTUALLY COUNTS BENEFITS - Kunertova, Dominika (Les ateliers de l'éthique / The Ethics Forum, 2018)
This paper aims to rethink the problem of NATO burden sharing along ethical lines. It argues that the ethics of burden sharing reveals the tensions between utility of contribution and fairness of distribution. Inspired by Jarrod Hayes and Patrick James’s theory-as-thought method and using the traditions of normative ethics, this interpretive research looks at how the issues of sharing and contributing were discursively framed by its practitioners during NATO’s first decade. Focusing on one of the largest founding members, Canada, the paper finds incoherence between the predominantly consequentialist discourse of government authorities with respect to Canada’s contributions and those authorities’ discourse on allied sharing in NATO, shaped by obligations and communitarian ethics. Consequently, this presence of different ethical logics points to a split discourse on NATO burden sharing in Canada. The paper sheds light on the normative roots of the burden-sharing problem and demonstrates the relevance of theoretical pluralism and eclectic methodology for foreign-policy analysis.